Rancang Bangun Aplikasi Point Of Sale Berbasis Web Studi Kasus Pada Toko Toys Amanah - Noviandri, Fajar; Fauziyah; Ulan Bani, Alexius; Joseph (Fakultas Teknik, Universitas Bhayangkara Jakarta Raya, 2022)
The development of information technology is growing so fast which has resulted in the emergence of increasingly fierce business competition. The application of information technology in the retail business can certainly help in simplifying and accelerating business processes. Toys Amanah is a family shop located on Jl. Kemandoran Pekayon RT 04/RW 023 Pekayon Jaya Village, South Bekasi District, Bekasi City, West Java Province. This shop sells a variety of toys and office stationery supplies. In its business process, this store still carries out sales transaction activities manually using receipts and notebooks for recording sales data and collecting data on goods. Therefore, in the transaction process, errors often occur in calculating the amount of money that must be paid by customers and it takes a lot of time to record reports and frequent inventory data errors that result in discrepancies between the inventory data and the physical goods. The next problem is that the store wants to give discounts to customers who often come in order to increase customer loyalty, but there is no system that can record loyal customers. In defining requirements and analyzing and designing systems for companies, data collection methods are needed by means of literature study, observation, interviews, design, implementation, and testing. For the analysis method and the concept of this information system, the unified modeling language (UML) model is used. The results of this study will be the construction of a web-based point of sale information system which is expected to be able to deal with the problems that exist in the store. This information system is made using the PHP programming language, MySQL database. With this point of sale information system, it can handle complaints experienced by the store in the process of the system running. Such as an error in the sales transaction process and data collection of goods and the length of time required to process sales reports.